Population analysis of total vibrio and heterotrophic bacteria in water and sediment to support intensive shrimp culture expansion in Pasangkayu Regency, West Sulawesi Province, Indonesia. Issue 1 (October 2021) - Paena, Mudian; Rante Tampangalo, Bunga; Kamariah,; Asaf, Ruzkiah; Athirah, Admi; Hasnawi,; Tarunamulia,; Indra Jaya Asaad, Andi; Ratnawati, Erna; Mustafa, Akhmad
Abstract: Shrimp is important aquatic food source for human around the world and cultured widely to fulfill shrimp demand that continues to increase along with the increased world's community. Shrimp is included in crustacea without adaptive immunity, which becomes the main problem that causes shrimp to be vulnerable against pathogenic infection and attack either from virus or bacteria as one of which is Vibrio harveyi . Vibrio harveyi are luminous Gram-negative heterotrophic bacteria that inhabit marine environment which represent a preference for temperate and tropical waters including Indonesian waters. Vibrio harveyi is one of pathogens that becomes the main failure in shrimp culture industry. Vibrio harveyi attacks host that has immune system disruption due to less water quality environment. Data and information about the existence of Vibrio bacteria in water area as this water area will be utilized as standard water source for shrimp culture activity, which becomes very important to determine the water management standard model and prevent disease and culture failure. Based on this condition, further study aimed was performed to identify the Vibrio harveyi and heterotrophic bacteria concentration in Pasangkayu District waters, West Sulawesi Province, Indonesia. The study was performed by the survey method. The study results showed that the total vibrio bacteria (TBV) in waters was among 2.25 × 10 2 – 1.51 × 10 4 cfu/mL, total heterotrophic bacteria (TPC) was among 7.19 × 10 3 – 9.04 × 10 3 cfu/mL. The TBV/TPC ratio in waters was among 6.53 – 10.62%. TBV in the sediment was among 3.5 × 10 1 -1 × 10 6 cfu/mL. TPC in the sediment was among 1.955 × 10 5 - 1 × 10 9 cfu/mL. The TBV/TPC ration in the sediment was among 0.20% - 14.20%. The vibrio bacteria can be used as low water quality bioindicator for main intensive culture pond water source when the TBV/TPC ratio in waters is above 10%. The TBV/TPC values in the Pasangkayu District waters were mostly still below 10%. This condition indicates intensive pond expansion possibility. To expand the culture pond without disrupting the water environmental balance, a preventive effort is required to suppress the TBV/TPC ratio by increasing the installation performance of organic waste processing in each intensive pond culture cluster.